Mathematical analysis of viscoelastic flows - Renardy, Michael (Society for Industrial and Applied Mathematics, 2000)
This monograph is based on a series of lectures presented at the 1999 NSF-CBMS Regional Research Conference on Mathematical Analysis of Viscoelastic Flows. It begins with an introduction to phenomena observed in viscoelastic flows, the formulation of mathematical equations to model such flows, and the behavior of various models in simple flows. It also discusses the asymptotics of the high Weissenberg limit, the analysis of flow instabilities, the equations of viscoelastic flows, jets and filaments and their breakup, as well as several other topics.
Keywords: Viscous flow.; Viscoelasticity.; elektronické knihy; electronic books